Confabulation and conversation. (February 2017) - Coltheart, Max
Abstract: Confabulation is sometimes defined – by Berlyne, for example – as a symptom that is seen only in one neuropsychological condition, amnesia. In this paper I argue for a somewhat more liberal – and, I contend, more productive – conception of confabulation, according to which it is seen not only in amnesia but also in other neuropsychological conditions such as delusion – and, indeed, even in healthy people. I also argue that it follows from this that in neuropsychological conditions where confabulations are seen, these are responses to abnormal experiences brought about by brain damage, but the occurrence of confabulation itself need not be seen as due to any impairment of cognitive processes due to the brain damage. It is instead a consequence of a general property of human cognition that is often referred to as "the drive for causal understanding".